A Comparison of Preterm Birth Rate and Growth from Birth to 18 Years Old between in Vitro Fertilization and Spontaneous Conception of Twins. (20th August 2021) - Zhang, Yali; Hong, Xuanming; Gao, Wenjing; Lv, Jun; Yu, Canqing; Wang, Shengfeng; Huang, Tao; Sun, Dianjianyi; Liao, Chunxiao; Pang, Zengchang; Yu, Min; Wang, Hua; et al.
Abstract: The aim of the present study was to compare the rate of preterm birth (PTB) and growth from birth to 18 years between twins conceived by in vitro fertilization (IVF) and twins conceived by spontaneous conception (SC) in mainland China. The retrospective cohort study included 1164 twins resulting from IVF and 25, 654 twins conceived spontaneously, of which 494 from IVF and 6338 from SC were opposite-sex twins. PTB and low birth weight (LBW), and growth, including length/height and weight, were compared between the two groups at five stages: infancy (0 year), toddler period (1–2 years), preschool (3–5 years), primary or elementary school (6–11 years), and adolescence (10–18 years). Few statistically significant differences were found for LBW and growth between the two groups after adjusting for PTB and other confounders. Twins born by IVF faced an increased risk of PTB compared with those born by SC (adjusted odds ratio [a OR ] 8.21, 95% confidence interval [CI] [3.19, 21.13], p < .001 in all twins and a OR 10.12, 95% CI [2.32, 44.04], p = .002 in opposite-sex twins). Twins born by IVF experienced a similar growth at five stages (0–18 years old) when compared with those born by SC. PTB risk, however, is significantly higher for twins conceived by IVF than those conceived by SC.